Parasitic Diseases of Indigenous Community (Kumal) in Nepal - Gyawali, P (Nepal Journal of Science and Technology, 2013)
Parasitic infection is common in indigenous community in low land of Nepal. Their life expectancy is well below in comparison to the other people. Kumal are disadvantaged group of people with low socio-economic condition. This study investigated helminthic infection in Kumal community in Gaidakot VDC, Chitwan district people. In this study 17% of total population of Kumal was selected and helminth parasitic eggs and larvae were detected by floatation method. Half of the study population had at least one helminthic parasite in their body. Hookworm was the most common parasites with 30.87% followed by Ascaris, Hymenolepsis, Trichuris, Strongyloide and Taenia with 16.10%, 6.04%, 3.35%, 2.68% and 2.01% respectively. Fourty years and older population were highly affected by helminths in both sexes. Single, double and multiple parasitic eggs also were recorded in the study population. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 175-178 DOI: http://dx.doi.org/10.3126/njst.v13i2.7731